Modelo Prolab: Andén, cadena de locales de venta de alimentos saludables - Cueva Torres, Estefany Rubi (2025)
This business model emerges as a solution to the identified social problem: the lack of hygiene in the handling and preparation of food in street food vendors, in addition to its high content of sugars and saturated fats, in Metropolitan Lima.. It was identified that the consumption of food in street food vendors is common among people aged 18 to 65 years of the B and C NSE, due to the lack of time to prepare food at home. Although the consumption of food in public spaces has advantages such as affordable prices and diversity, it also poses significant risks to public health. In Lima, 42% of the population leaves home at least once a week, which represents a business opportunity for proposals that will offer safe and nutritious food. In this sense, the "Anden" business proposal is presented, which seeks to position itself as a chain of stores that offers a comprehensive customer experience, combining elements of comfort and safety with the sale of nutritious and healthy food, prepared with high-quality Peruvian ingredients, nutritional content, and served in just a few minutes, without compromising quality or strict sanitation protocols. Its objective is to satisfy the needs of those who want fast, quality food, with high hygiene standards and affordable prices. Finally, the financial viability of the proposal is validated with a financial NPV of S/ 5,922,462 and an IRR of 68%; also, a social NPV of S/ 5,610,729; which shows that “Anden” is a viable solution, and the desirability hypotheses are also validated through experimentation.